Associations among stressors, perceived stress, and psychological distress in nursing students: a mixed methods longitudinal study of a Hong Kong sample - Cheng, Winnie Lai Sheung; Chow, Peggy Pik Kei; Wong, Florence Mei Fung; Ho, Mandy Man (Frontiers in Psychology, 2023)
A longitudinal design, using questionnaires and focus group interviews of a single cohort of nursing students in Hong Kong and following them over their five years of training. The Stressors in Nursing Students Scale-Chinese version and the Chinese version of General Health Questionnaire-12 were used to assess stress levels and psychological distress, respectively.Ninety-seven participants completed the questionnaires 5 times. Quantitative findings revealed that the overall stress levels of the nursing students increased over five years (from mean=3.08 to 3.33), with the highest levels in the second wave (mean=3.33). Nursing students experienced higher stress during years 2 (p=0.006) and 4 (p=0.037). Psychological distress was the highest in year 3 (sum score=18.47) (p=0.002) but declined from year 4 (p<0.001). Thematic analysis revealed that academic performance issues, coping challenges, unfavorable learning environments, relationships were identified as the stressors. However, nursing students also used positive coping strategies to pursue success and seek support.This study suggests that the year of study is a significant predictor of stress levels among nursing students, especially during the first and senior years due to heavy academic workload. Psychological distress was observed among nursing students, and those who worked more part-time jobs tended to report higher levels of distress. The junior year was associated with higher levels of distress related to financial and time-related stress, while academic and personal problems were more prevalent during the senior year.